2014
DOI: 10.1007/s11069-014-1479-7
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the impact of urbanization on energy consumption in Jiangsu Province

Abstract: Jiangsu is one of the most developed regions in China. Its' urbanization rate increased to 61.9 % in 2011, faster than the whole country level (51.27 %). Exploring the influence of urbanization on energy consumption in Jiangsu may help find the relationship between energy consumption and urbanization. The main results received in this paper are as follows.(1) Urbanization accelerated the produce energy consumption over the study period. The produce energy consumption jumped from 50.7 Mtce in 1995 to 166.6 Mtce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(21 reference statements)
1
4
1
Order By: Relevance
“…Consistent with Zhang and Li [28], Fan et al [44], and Chen et al [83], a positive relationship is found between the urbanization rate and REC in the present study. Te infuence of the urbanization rate on REC is related to economic development and the degree of urbanization [26,84].…”
Section: Analysis Of the Impact Factorssupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with Zhang and Li [28], Fan et al [44], and Chen et al [83], a positive relationship is found between the urbanization rate and REC in the present study. Te infuence of the urbanization rate on REC is related to economic development and the degree of urbanization [26,84].…”
Section: Analysis Of the Impact Factorssupporting
confidence: 92%
“…Province located in the eastern coastal center of the Chinese mainland (see Figure 2) and one of the most developed areas in China [28]. As with many other Chinese provinces, since the turn of the 21st Century, its economy's continued rapid development [29] has created serious ecological problems [30], which have led to the need to consider the issue of saving energy and protecting the environment when pursuing economic development.…”
Section: Te Study Area Te Focus Of This Study Is On Jiangsumentioning
confidence: 99%
“…With sufficient water vapor, the ExHP event is likely to occur in urban. Moreover, the circulation characteristics caused by the UHI effect in the Shenyang municipal district are also seen in Beijing, Shanghai, Jiangshu and other areas (Zhang, 2012;Zhu et al, 2018;Hou et al, 2019).…”
Section: Figure 16mentioning
confidence: 99%
“…Sadorsky (2014) used panel data on 18 emerging economies from 1971 to 2008, investigated the influence of income, urbanization and industrial development on ENC and reported that urbanization instigated a decline in energy use in the long run, while income augmented the latter in both the long and short run. Zhang and Li (2015) examined the urbanization process in Jiangsu regions in China, investigated the impact of urbanization on ENC over the period 1997-2012 and discovered that urbanization augmented the produced ENC. Azam et al (2016) examined the macroeconomic determinants of ENC in Greece.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Zhang and Li (2015) examined the urbanization process in Jiangsu regions in China, investigated the impact of urbanization on ENC over the period 1997–2012 and discovered that urbanization augmented the produced ENC. Azam et al (2016) examined the macroeconomic determinants of ENC in Greece.…”
Section: Literature Reviewmentioning
confidence: 99%